Sharing Is Caring: Employee Stock Ownership Plans and Employee Well-Being in U.S. Manufacturing - Adrianto Adrianto; Avner Ben-Ner; Jason Sockin; Ainhoa Urtasun (Institute of Labor Economics (IZA), 2024)
Do employees fare better in firms they partly own? Examining workers' reviews of their employers on Glassdoor, we compare employee satisfaction between firms in which workers own company shares through an employee stock ownership plan (ESOP) and conventional firms in which they do not. Focusing on workers in U.S. manufacturing, we find employees report greater satisfaction in employee-owned firms overall and with specific aspects of jobs such as firm culture. This satisfaction premium is greater when the ESOP is the product of collective bargaining or employees own a larger stake of firm equity. Employee well-being can thus differ by ownership arrangement.
Keywords: J52; J28; M14; 330; ESOP; job satisfaction; collective bargaining; culture